Greek Onomastics, Phraseology, Indo-European Poetic Language: towards a reelaboration of Fr. Bechtel’s Die historischen Personennamen des Griechischen (Atti del Sodalizio Glottologico Milanese, 2021)
The present paper relies on the materials from the files for a reelaboration of Friedrich Bechtel’s epoch-making Die historischen Personennamen des Griechischen (1917: HPNG), that, having basically the same structure as HPNG, will integrate the names of the 1st millenium, which were still not known at its time, and those attested in Linear B, as well as the phraseological collocations, poetic or prosaistic, underlying them, which were taken into account only sporadically in HPNG, and, if possible, their parallels and eventual IE background. The names discussed are classified into three groups: those attested only in 1st millennium Greek, those attested also in Mycenaean, and those attested exclusively in Mycenaean. Special attention is dedicated to four names which reflect inherited lexicon and Indo-European poetic phraseology, namely Ἁρμόδικoς (and Ἁρμoδίκᾱ), Βοᾱ́θοος, Εὐρυφάων (and Εὐρύφαντος), and Φέριστος, Φέρτατος.